The role of the household in the social inclusion of children with special needs in Uganda - a photovoice study - Caroline Masquillier; Sara De Bruyn; David Musoke (BMC, 2021)
Abstract Background Social inclusion establishes a basis for the overall wellbeing of children with special needs. Although children's lives are centred around the household, little is known about the household's influence on social inclusion. Therefore, the aim is to investigate the household's role in the social inclusion of children with special needs in Uganda. Methods Twelve carers of children with special needs participated in this photovoice study on the outskirts of Kampala, Uganda - including a training workshop, home visits, in-depth individual interviews and focus group discussion. Results The social inclusion of children with special needs is highly complex because it has the potential to both benefit and cause harm. The results show that when a disability is socially devalued to a certain degree, carers and their household members have to deal with the ongoing process of stigma management. Depending on the characteristics of the child, carer and household, this can lead to an upward spiral towards visibility or a downward spiral towards concealment - reinforcing social inclusion or stigma, respectively. Conclusions Despite the fact that there is disability among Ugandan children it remains a 'hidden reality'. This research helps to reveal this hidden reality by understanding the role of the household in social inclusion in a stigmatized context.